1981
DOI: 10.1073/pnas.78.6.3305
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of the primary state, P F , of bacterial photosynthesis

Abstract: We have obtained the magnetic resonance spectrum of the radical pair state pF by using reaction yield detected magnetic resonance spectroscopy. The magnetic resonance spectrum is quite sensitive to the local environment of pF. The data place limits on the lifetime of triplet pF and the distance of charge separation.(24). Optical measurements of the pR yield upon recombination show large magnetic field effects and have become one method of studying the radical pair state. In addition, we have found by optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…1) (1,2). In the present paper we demonstrate that the quantum yield of this triplet state, (DT, depends on the orientation of the RCs in a magnetic field.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…1) (1,2). In the present paper we demonstrate that the quantum yield of this triplet state, (DT, depends on the orientation of the RCs in a magnetic field.…”
mentioning
confidence: 84%
“…The effect of varying the polarization of the excitation pulse, ,1e is much smaller. I(H, the o 710) = S(H, tnei rio)/S(0, 'te' 'T0) [1] (H. e) I(H, nef0) -I(Hne900) [2] I(H,n1000) + 2 I(H, ne,900) [3] Because the relative yields, I(H,nieno), are defined as ratios, the effect of the field-independent photoselection is not in- If absorption at 532 nm were isotropic, the observation anisotropy, ao(H,q1e), would be independent of Be and the excitation anisotropy, ae(H,nr0), would be zero at all fields. Both of these conditions are approximately satisfied by the data in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The data to be evaluated in this paper were obtained by a previously described experimental technique (5) In addition, because the RYDMR linewidth is due only to a short lifetime for triplet pF (essentially our conclusion in this paper), then, if the electron spin-spin interactions were less than the hyperfine interactions, it would logically follow that the RC PF system would optically display a lifetime much shorter than 10-20 nsec. We note that the isotropic exchange interactions are known to be quite weak from previous work (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…To investigate this, a low power, low magnetic field RYDMAR method was devised (Mohl et al, 1985). In addition, in this technique continuous illumination was employed, leading to a much higher signal-to-noise ratio than in the time-resolved technique of Bowman et al (1981). Lineshapes of the R Y D M A R resonance were observed that conformed very well to those theoretically predicted (Lersch et al, 1982; cessful RYDMAR experiment on photosynthetic R C , Michel-Beyerle, 1983;Tang and Norris, 1983).…”
Section: Reaction Yield Detected Magnetic Resonance ( R Y D M a R )mentioning
confidence: 51%
“…Ito> remains degenerate with IS>, but it can be shown that in contrast to the Itk> levels the It,> level has zero I To> character, because its axis of quantization is perpendicular to that of the IT,> level ( B , I I?,) (Lersch and Michel-Beyerle, 1983 yield, compared to the value at B, for B 1 = 0, has been observed (Bowman et al, 1981). When B1 < ]Dl,/JI the situation is much more complex, the shape and sign of the RYDMAR signal being very sensitive to J (Lersch and Michel-Beyerle, 1983).…”
Section: Reaction Yield Detected Magnetic Resonance ( R Y D M a R )mentioning
confidence: 92%